Given the function:
![r(x)=x^3-4x^2_{}+4x-6](https://img.qammunity.org/2023/formulas/mathematics/college/7k8jsmwbm0rbqm56jt4d228ltivwrw0oz1.png)
We are required to find the value of r(2).
This simply means we must substitute x = 2 wherever we see x in the function r(x).
This is done below:
![\begin{gathered} r(x)=x^3-4x^2+4x-6 \\ \text{substitute x = 2} \\ r(2)=2^3-4(2)^2+4(2)-6 \\ \\ \therefore r(2)=8-16+8-6 \\ r(2)=-6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/hchvqtge89ac9ksy14wzqx8swzvdgvw6q4.png)
Therefore, r(2) = -6.
Step-by-step explanation:
Because when x = 2, r(2) = -6, it means that we can re-write x = 2 as:
![\begin{gathered} x=2 \\ \text{subtract 2 from both sides} \\ x-2=2-2 \\ x-2=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/o9c8jxqu7pxnweh1q5zghdimu1m13mepfh.png)
If r(2) were equal to zero i.e. r(2) = 0, it would have been a factor of r(x). But because
r(2) = -6, it means that (x - 2) divides r(x) and gives a remainder of -6.
Hence, (x-2) divides r(x) and leaves a remainder of -6